ASSESS THE KNOWLEDGE AND ATTITUDE OF PREGNANT WOMEN ABOUT RISK FACTORS DURING PREGNANCY IN LAKHODAIR COMMUNITY HEALTH CENTER (Journal of Medical & Health Sciences Review, 2025)
Knowledge regarding maternal risk factors among pregnant women ultimately overcomes the likelihood of adverse events in pregnancy and childbirth. This study aimed to explore Lakhodair community pregnant women's knowledge and attitudes about maternal risk factors in pregnancy. A single-center cross-sectional survey was conducted from 8th March to 13th June 2024 among women of reproductive age (15-49 years). A convenient sampling technique was used to recruit the sample and data was collected using an adopted structured questionnaire. SPSS version 20 was used to analyze the data. Data from 92 women underwent final analysis. The mean age of respondents was 26-35 years (52.2%). Most of the respondents (89.10%) correctly knew the maternal risk factors in pregnancy. A large percentage of women knew that poor nutrition, anemia (93.5%), smoking and passive smoke (92.4%), and obesity (87.0%) during pregnancy were risk factors affecting the fetus's health. However, the overall attitude of pregnant women towards pregnancy risk factors is positive, about (70.7 %) of women mentioned pregnancy does not cause any harm. So, there was no need for medical check-ups regularly. In conclusion, Lakhodair community pregnant women demonstrated a good level of knowledge and positive attitude regarding the risk factors during pregnancy.